GROUND-BASED ACOUSTIC IMPACT ON THE ATMOSPHERE: THE RESULTS OF OBSERVATIONS BY MEANS OF INCOHERENT SCATTER AND VERTICAL SOUNDING TECHNIQUES - Emelyanov, L. Ya.; Zhivolup, T. G.; Soroka, S. A.; Cheremnykh, O. K.; Chernogor, L. F. (Видавничий дім «Академперіодика», 2015)
The results of the experiment on investigation of ionosphere response to acoustic impacts are presented. The experiment was carried out by the Lviv Centre of the Institute for Space Research (LC ISR) and the Institute of Ionosphere (Kharkiv) in 2006. The LC ISR equipment set at the Ionospheric Observatory of the Institute of Ionosphere was used as a source of acoustic signal. Diagnostics of changes in the ionosphere was carried out by the incoherent scatter radar with the zenith antenna and by the “Basis” ionosonde of the Institute of Ionosphere, as well as by the monitoring equipment of LC ISR. Some changes in parameters of the ionosphere at altitudes of 160-200 km that followed after the acoustic signal impact on the atmosphere were found.Key words: acoustic impact, ionosphere, incoherent scatter method, vertical sounding techniqueManuscript submitted 15.10.2014Radio phys. radio astron. 2015, 20(1): 37-47REFERENCES1. SPECIAL ISSUE EVOTED TO MASSAPROJECT, 1985. Izv. AN SSSR. Physics of the Earth. no. 11, pp. 3–112 (in Russian). 2. GARMASH, K. P., GRITCHIN, A. I., LEUS, S. G., PAKHOMOVA, O. V., POKHIL'KO, S. N. and CHERNOGOR, L. F., 1994. Investigation of the ionospheric plasma response to the impact of groundwater, surface air explosions and earthquakes. In: Fizika kosmicheskoj plazmy. Kiev, Ukraine: NKAU Publ., pp. 151–160 (in Russian). 3. CHERNOGOR , L. F., 2003. Physics of Earth, Atmosphere, and Geospace from the Standpoint of System Paradigm. Radio Phys. Radio Astron. vol. 8, no. 1, pp. 59–106 (in Russian). 4. CHERNOGOR, L. F., 2006. Earth–atmosphere–ionosphere–magnetosphere as an open dynamic nonlinear physical system (Part 1). Nelinejnyj mir. vol. 4, no. 12, pp. 655–697 (in Russian). 5. CHERNOGOR, L. F., 2007. Earth–atmosphere–ionosphere–magnetosphere as an open dynamic nonlinear physical system (Part 2). Nelinejnyj mir. vol. 5, no. 4, pp. 198–231 (in Russian). 6. CHERNOGOR , L. F., 2008. On the Nonlinearity in Nature and Science. Kharkiv, Ukraine: V. N. Karazin Kharkiv National Universine Publ. (in Russian). 7. CHERNOGOR , L. F., 2009. Radiophysical and Geomagnetic Effects of Rocket Launch. Kharkiv, Ukraine: V. N. Karazin Kharkiv National Universine Publ. (in Russian). 8. CHERNOGOR , L. F., 2012. Physics and Ecology of Disasters. Kharkiv, Ukraine: V. N. Karazin Kharkiv National Universine Publ. (in Russian). 9. TARAN, V. I., POD'YACHIY, Yu. M., SMIRNOV, A. N. and GERSHTEIN, L. Ya., 1985. Ionospheric Dist Urbances after a ground explosion from observations by incoherent scatter method. Izv. AN SSSR. Physics of the Earth. no. 11, pp. 75–79 (in Russian). 10. DOMNIN, I. F., PANASENKO, S. V., URYADOV, V. P. and CHERNOGOR, L. F., 2012. Results of Radio physical Study of Wave Disturbances in the Ionospheric Plasma During Its Heating by High-Power HF Radio Transmission of "Sura" facility. Radiophys. Quantum Electron. vol. 55, no. 4, pp. 253–265. DOI: https://doi.org/10.1007/s11141-012-9364-2 11. KOSHOVYI, V. V. and Soroka, S. O., 1998. Acoustic disturbance of ionospheric plasma by a ground-based radiator. Kosmichna nauka i tekhnologiya. vol. 4, no. 5/6, pp. 5–17 (in Russian). DOI: https://doi.org/10.15407/knit1998.05.003 12. KOSHOVY, V. V., 1999. Radiophysical and radioastronomical diagnostics of ionospheric effects induced by a ground-based infrasonic transmitter (preliminary results). Radiophys. Quantum Electron. vol. 42, is. 8, pp. 691–704. DOI: https://doi.org/10.1007/BF02676855 13. NAZARCHUK, Z. T., KOSHEVYI, V. V., SOROKA, S. A., IVANTISHIN, O. L., LOZINSKY, A. B. and ROMANISHYN, I. M., 2003. On acousto-electromagnetic u1079 sounding of ionosphere. Kosmichna nauka i tekhnologiya. vol. 9, no. 2 suppl., pp. 17–23 (in Russian). 14. Lysenko, V. N., Soroka, S. A., Taran, V. I., Tyrnov, O. F. and Chernogor, L. F., 1996. Integrated observations of dynamic processes in the atmosphere-ionosphere-magnetosphere system accompanying the acoustic influence upon the surface atmosphere. 1. Scientific and practical significance. In: 6th Ukrainian Conference on Space Research Proceedings. Evpatoria, Ukraine, p. 69 (in Russian). 15. GARMASH, K. P., EMELYANOV, L. Ya., KALITA, B. I., KOSTROV, L. S., LYSENKO, V. N., NOGACH, R. T., PANASENKO, S. V., SKLYAROV, I. B., SOROKA, S. A., TARAN, V. I., TYRNOV, O. F. and CHERNOGOR, L. F., 1996. Integrated observations of dynamic processes in the atmosphere-ionosphere-magnetosphere system accompanying the acoustic influence upon the surface atmosphere. 2. Facilities and methods. In: 6th Ukrainian Conference on Space Research Proceedings. Evpatoria,Ukraine, p. 70 (in Russian) 16. GARMASH , K. P., KALITA, B. I., NOGACH, R. T., SOROKA, S. A. and CHERNOGOR, L. F., 1996. Integrated observations of dynamic processes in the atmosphere-ionosphere-magnetosphere system accompanying the acoustic influence upon the surface atmosphere. 3. Processes in the atmosphere and geomagnetic field. In: 6th Ukrainian Conference on Space Research Proceedings. Evpatoria, Ukraine, p. 71 (in Russian). 17. GARMASH, K. P., PANASENKO, S. V., SOROKA, S. A., TYRNOV, O. F. and CHERNOGOR, L. F., 1996. Integrated observations of dynamic processes in the atmosphere-ionosphere-magnetosphere system accompanying the acoustic influence upon the surface atmosphere. 4. Processes in the mesosphere. In: 6th Ukrainian Conference on Space Research Proceedings. Evpatoria, Ukraine, p. 72 (in Russian) 18. EMELYANOV, L. Ya., KOSTROV, L. S., LYSENKO, V. N., SOROKA, S. A., TARAN, V. I., TYRNOV, O. F. and CHERNOGOR, L. F., 1996. Integrated observations of dynamic processes in the atmosphere-ionosphere-magnetosphere system accompanying the acoustic influence upon the surface atmosphere. 5. Processes in the ionosphere. In: 6th Ukrainian Conference on Space Research Proceedings. Evpatoria, Ukraine, p. 73 (in Russian) 19. GARMASH, K. P., EMELYANOV, L. Ya., KALITA, B. I., KOSTROV, L. S., LYSENKO, V. N., NOGACH, R. T., PANASENKO, S. V., SKLYAROV, I. B., SOROKA, S. A., TARAN, V. I., TYRNOV, O. F. and CHERNOGOR, L. F., 1996. Integrated observations of dynamic processes in the atmosphere-ionosphere-magnetosphere system accompanying the acoustic influence upon the surface atmosphere. 6. Basic results. In: 6th Ukrainian Conference on Space Research Proceedings. Evpatoria, Ukraine, p. 74 (in Russian) 20. TARAN, V. I., 2001. Study of the ionosphere in the natural and artificially excited states by method of incoherent scattering. Geomagnetizm i Aeronomya. vol. 41, no. 5, pp. 659–666 (in Russian). 21. Schunk, R. W. and Nagy, A. F., 2000. Ionospheres: Physics, Plasma Physics, and Chemistry. Cambridge, UK: Cambridge University Press.https://doi.org/10.1017/CBO9780511551772 22. ANTONOVA, L. A. and IVANOV-KHOLODNY, G. S., 1988. The F1-layer. Appearance Conditions and Height. Geomagn. Aeron. vol. 28, no.6, pp. 940–944 (in Russian). 23. ANTONOVA, L. A. and IVANOV-KHOLODNY, G. S., 1989. Solar activity and ionosphere (at heights of 100–200 km). Moscow, Russia: Nauka Publ. (in Russian).